2021
DOI: 10.1039/d1tc01538a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of silicon-vacancy center formation during the CVD diamond growth of thin and delta doped layers

Abstract: The results of a study of the deposition of silicon-doped epitaxial diamond layers in a microwave CVD reactor to create silicon-vacancy color centers are presented. The relationship between the optical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…[ 7 ] The latter method does not damage the diamond crystal lattice and makes it possible to create SiV centers at any depth in the epitaxial layer. In our work, [ 8 ] we demonstrated the creation of a delta layer doped with silicon with a thickness of about 5 nm using the CVD method. This method of creation of SiV centers makes it possible to position them along the depth of the epitaxial layer with nanometer accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 7 ] The latter method does not damage the diamond crystal lattice and makes it possible to create SiV centers at any depth in the epitaxial layer. In our work, [ 8 ] we demonstrated the creation of a delta layer doped with silicon with a thickness of about 5 nm using the CVD method. This method of creation of SiV centers makes it possible to position them along the depth of the epitaxial layer with nanometer accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In these works, it was found that the dependence of the emission intensity of SiV centers on the percent ratio of silicon to carbon in the Si/C gas mixture has a nonmonotonic form. [ 8,11–13 ] With an increase of the Si/C ratio, the emission intensity of SiV centers in diamond first increases to a maximum value, which is observed at Si/C = 0.1%–2%, [ 8,11–13 ] and then decreases. Such a decrease of the emission intensity of SiV centers, as shown in ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the spin state of the NV À center can easily be initialized and read out along with a long coherent time, which shows promising potential in the area of quantum communication. [9][10][11] The optical emission of SiV À centers exhibits a narrow ZPL width at room temperature that concentrates more than 70% of its signals, 12,13 which is a promising candidate for the application of a room-temperature single photon source. [14][15][16] And their different charged states could be mutually switched to each other.…”
Section: Introductionmentioning
confidence: 99%